1989
DOI: 10.1007/bf01990459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of butyrate and insulin and their interaction on the DNA synthesis of rumen epithelial cells in culture

Abstract: Rumen epithelial cells (REC) were incubated in the presence of various concentrations of butyrate or insulin or with both of them, to obtain information on their effect on the DNA synthesis of cultured cells. The 24-h values of 3H-thymidine incorporation into cellular DNA were measured in the presence of butyrate, insulin or butyrate plus insulin. While butyrate reduced DNA synthesis, insulin produced an increase over the control. Combined butyrate plus insulin treatment influenced the incorporation of label i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The reduction of apoptosis is another important factor that can increase cell accumulation in rumen mucosa (32,36,45). For example, by downregulation of IGFBP3, butyrate is thought to slow apoptosis, thereby encouraging rumen tissue growth (32,45).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of apoptosis is another important factor that can increase cell accumulation in rumen mucosa (32,36,45). For example, by downregulation of IGFBP3, butyrate is thought to slow apoptosis, thereby encouraging rumen tissue growth (32,45).…”
Section: Discussionmentioning
confidence: 99%
“…Feeding induced adaptations of rumen epithelium growth are largely due to propionate and butyrate in the rumen fluid [34,35,41,68,85,101]. In the 1980's, German and Israeli scientists [27,71,78] showed that a reduction takes place in the surface area of the rumen papillae due to reduced feed intake in the dry period, and that this reduction could partly be prevented by giving an energy-rich lactation feed throughout the dry period.…”
Section: Rumen Epitheliummentioning
confidence: 99%
“…Daily fluctuations in butyrate concentration have a very pronounced positive effect on the proliferation of the ruminal epithelium in 6itro (Sakata & Tamate, 1978). The positive effect of propionate and butyrate on proliferation could be explained by the metabolization of the VFA in the ruminal mucosa (Sander et al, 1959), the indirect effect of VFA on blood flow in the mucosa (Fell & Weekes, 1975) or the indirect effect of butyrate and propionate on insulin secretion (Brockman, 1984), which has a positive effect on cell proliferation in the rumen epithelium in sheep (Sakata & Tamate, 1978, 1979Neogrady et al, 1989).…”
Section: Introductionmentioning
confidence: 99%